GaAs membrane PhC lasers threshold reduction using AlGaAs barriers and improved processing. (1st January 2023) - Flores Esparza, Sergio Iván; Lecestre, Aurélie; Dubreuil, Pascal; Arnoult, Alexandre; Mlayah, Adnen; Monmayrant, Antoine; Gauthier-Lafaye, Olivier
Abstract: Active suspended membranes are an ideal test-bench for experimenting with novel laser geometries and principles. We show that adding thin AlGaAs barrier near the top and bottom Air/GaAs interfaces of the membrane significantly reduces the carriers non-radiative recombinations and decreases the threshold of test photonic crystal test lasers. We review the existing literature on photonic crystal membrane fabrication and propose an overview of the significant defects that can be induced by each fabrication step. Finally we propose a complete processing scheme that overcome most of these defects.